Advanced Intelligent Computing Theories and Applications 6th International Conference on Intelligent Computing, ICIC 2010, Changsha, China, August 18-21, 2010. Proceedings - Huang, De-Shuang.; Zhao, Zhongming; Bevilacqua, Vitoantonio; Figueroa, Juan Carlos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Conference on Intelligent Computing, ICIC 2010, held in Changsha, China, in August 2010. The 85 revised full papers presented were carefully reviewed and selected from a numerous submissions. The papers are organized in topical sections on neural networks, evolutionary learning & genetic algorithms, fuzzy theory and models, fuzzy systems and soft computing, particle swarm optimization and niche technology, supervised & semi-supervised learning, unsupervised & reinforcement learning, combinatorial & numerical optimization, systems biology and computational biology, neural computing and optimization, nature inspired computing and optimization, knowledge discovery and data mining, artificial life and artificial immune systems, intelligent computing in image processing, special session on new hand based biometric methods, special session on recent advances in image segmentation, special session on theories and applications in advanced intelligent computing, special session on search based software engineering, special session on bio-inspired computing and applications, special session on advance in dimensionality reduction methods and its applications, special session on protein and gene bioinformatics: methods and applications.
Neural Networks -- Evolutionary Learning and Genetic Algorithms -- Fuzzy Theory and Models -- Fuzzy Systems and Soft Computing -- Particle Swarm Optimization and Niche Technology -- Supervised and Semi-supervised Learning -- Unsupervised and Reinforcement Learning -- Combinatorial and Numerical Optimization -- Systems Biology and Computational Biology -- Neural Computing and Optimization -- Nature Inspired Computing and Optimization -- Knowledge Discovery and Data Mining -- Artificial Life and Artificial Immune Systems -- Intelligent Computing in Image Processing -- Special Session on New Hand-Based Biometric Methods -- Special Session on Recent Advances in Image Segmentation -- Special Session on Theories and Applications in Advanced Intelligent Computing -- Special Session on Search Based Software Engineering -- Special Session on Bio-inspired Computing and Applications -- Special Session on Advance in Dimensionality Reduction Methods and Its Applications -- Special Session on Protein and Gene Bioinformatics: Methods and Applications.
Keywords: Computer science; Information systems; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Information Systems Applications (incl.Internet).; Image Processing and Computer Vision; Computation by Abstract Devices; User Interfaces and Human Computer Interaction